2022
DOI: 10.1177/02692155221080546
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of adding virtual reality to physiotherapeutic treatment in patients with total hip arthroplasty. A randomized controlled trial

Abstract: Objective To determine the clinical effectiveness of adding virtual reality via the Nintendo Wii console and its Wii Balance Board to physiotherapy treatment in patients with total hip arthroplasty. Design Randomized controlled trial. Setting Clinical Hospital San Borja Arriaran, Santiago, Chile. Participants A total of 73 patients over 50 years of age with total hip arthroplasty were randomly allocated to two groups. Interventions The control group (n = 37) received 6 weeks of physiotherapy treatment; the int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 34 publications
(56 reference statements)
0
8
0
Order By: Relevance
“…In addition, it has been reported that the weight load between the lower limbs changes, which increases the strength capacity of the hip joint–stabilizing muscle tissue and adversely affects the function of these patients. Zavala-González et al [ 37 ] explored the clinical effects of applying VR technology in the physical therapy of patients who underwent total hip arthroplasty by means of the Nintendo Wii game console and its Wii Balance Board. In the short term, the addition of VR by means of Nintendo Wii and its Wii Balance Board platform resulted in statistically significant differences in the functioning of patients who underwent total hip replacement, but these differences were not clinically important.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, it has been reported that the weight load between the lower limbs changes, which increases the strength capacity of the hip joint–stabilizing muscle tissue and adversely affects the function of these patients. Zavala-González et al [ 37 ] explored the clinical effects of applying VR technology in the physical therapy of patients who underwent total hip arthroplasty by means of the Nintendo Wii game console and its Wii Balance Board. In the short term, the addition of VR by means of Nintendo Wii and its Wii Balance Board platform resulted in statistically significant differences in the functioning of patients who underwent total hip replacement, but these differences were not clinically important.…”
Section: Resultsmentioning
confidence: 99%
“…After the full text was assessed, 10 articles were excluded because they did not conform to the eligibility criteria. Finally, 11 studies [16][17][18][19][20][21][22][23][24][25][26] were included in this study. Among these studies, a total of 1327 patients were included; there were 634 cases in the intervention group and 693 patients in the control group.…”
Section: Literature Search and Characteristics Of The Included Studiesmentioning
confidence: 99%
“…Ten RCTs [16][17][18][19][20][21][22][23][24][25] reported random sequence generation. Seven RCTs [16][17][18]20,21,23,25] reported allocation concealments. Four RCT [16][17][18]23] outcome assessors were blinded.…”
Section: Quality Assessment Of the Included Studiesmentioning
confidence: 99%
See 2 more Smart Citations